Critical care nurses' perceptions toward withdrawal of life-sustaining treatments: a phenomenology study - Alabd, Ibrahim Ahmd; Mohammad, Sahar Yassien; Ameen, Dalia Ali (Jurnal Ners, 2024)
Introduction: Withdrawing life-sustaining measures involves complex legal and ethical considerations, and few healthcare providers have received specialized training in this area. This study explored critical care nurses' perceptions of withdrawing life-sustaining treatment. Methods: A qualitative phenomenological design was used, a purposive sample of 15 individuals of both sexes for nurses working in the ICU for at least six months. The study was conducted in seven critical care units at four hospitals at Ain Shams University. The data collection process involved audio recordings of semi-structured open-ended interviews and the data were analyzed based on Tesch’s method. Results: Study results revealed that the sample age ranged from 24 to 38 and ranged from 1 year to 14 years working in ICU at various levels starting from nursing staff to head nurses. Critical care nurses' perceptions were reflected through four main themes and related subthemes. The main themes that shaped nurses' perceptions were attitudes toward withholding and withdrawing life-sustaining treatments, ethical perceptions, beliefs impact, and legal framework. Conclusions: Nurses face difficult experiences influencing their perceptions of life-sustaining treatment withdrawal, emphasizing the importance of policy guidance to prevent decisions based only on beliefs. Therefore, further qualitative and quantitative studies are required. Keywords: life-sustaining treatments, Perceptions, qualitative design, themes, withdrawal